Penggabungan Algoritma Hill Cipher dan ElGamal untuk Mengamankan Pesan teks - Fadlilah, Siti Nur; Turmudi, Turmudi; Khudzaifah, Muhammad (Jurnal Riset Mahasiswa Matematika, 2022)
Hill Cipher is a one of the symmetric key cryptography algorithm that using an invertible matrix with an order n×n as a key to encrypt and decrypt plaintext. Meanwhile, ElGamal is other asymmetric key cryptography algorithm that use the complexity of discrete logarithms in the encryption and decryption process. In this study, the authors are interest in combine the Hill Cipher and ElGamal algorithms to secure text messages. The author use the matrix as a symmetric key and converts the plaintext in the table of ASCII 256. Then encrypt using the Hill Cipher algorithm which results the ciphertext from messages and ElGamal algorithm results the ciphertext of the symmetric key. In processing decryption using the ElGamal algorithm to determine the symmetric key that will be used as a key in the decryption process with the Hill Cipher algorithm so that the original plaintext is obtained. Then the results obtained are that the combination of the Hill Cipher and ElGamal algorithms to secure text messages can be done it well.